2023
DOI: 10.1039/d3cb00081h
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and challenges associated with bisulfite-assisted nanopore direct RNA sequencing for modifications

Aaron M. Fleming,
Judy Zhu,
Vilhelmina K. Done
et al.

Abstract: Nanopore direct RNA sequencing is a technology that allows the interrogation of the sequence information for epitranscriptomic modifications with the possibility of a quantitative assessment. The 113 pseudouridine (Ψ) sites...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 70 publications
(244 reference statements)
0
10
0
Order By: Relevance
“…[34,[44][45][46] We applied this approach to determine that stable bisulfite adducts to Ψ impact the ion current significantly such that the base call algorithm fails to provide a base call for the modification resulting in a deletion error for its presence in the RNA. [34] Further, this approach gives a positive signal change to minimize the false discovery rate of nanopore sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…[34,[44][45][46] We applied this approach to determine that stable bisulfite adducts to Ψ impact the ion current significantly such that the base call algorithm fails to provide a base call for the modification resulting in a deletion error for its presence in the RNA. [34] Further, this approach gives a positive signal change to minimize the false discovery rate of nanopore sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…3 The pH 7 bisulfite reaction to yield Ψ adducts results in detection of adducts via a deletion signature in traditional sequencing after reverse transcription, 1,22,23 and it is found as an indel in nanopore direct RNA sequencing. 51 In the nanopore data, the indel results from the current levels being poorly recognized by the software. Future developments in nanopore data analysis software will allow this modified nucleotide and likely others to be directly sequenced.…”
Section: Discussionmentioning
confidence: 99%
“…coli. , The occupancy of Ψ across the transcriptome is organism, cell-type, and stress-dependent, suggesting that this U isomer has a significant role in cellular processes. ,,,, Determination of these roles will require accurate and quantitative sequencing of RNA, in which nanopore direct RNA sequencing is a candidate method to achieve this goal. , Our work identified that nanopore signatures for Ψ are highly sequence context dependent and that using a consensus of nanopore current, helicase dwell time, and base miscalling is an approach to sequence this U isomer . The pH 7 bisulfite reaction to yield Ψ adducts results in detection of adducts via a deletion signature in traditional sequencing after reverse transcription, ,, and it is found as an indel in nanopore direct RNA sequencing . In the nanopore data, the indel results from the current levels being poorly recognized by the software.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations